(untitled) (Dhaka University Law Journal, 2024)
The effects of globalization on labor standards and working conditions have been widely debated, with some arguing that globalization has improved labor standards and working conditions while others claim it has led to a deterioration of such standards. This paper aims to explore the effects of globalization on labor standards and working conditions. The study will examine the impact of globalization on the labor market, focusing on changes in labor laws and regulations, worker rights, and wages. The research will also investigate the impact of globalization on working conditions, including workplace safety and health, and the quality of jobs. Furthermore, the study will explore the role of multinational corporations in shaping labor standards and working conditions in different countries. The findings of this research will provide insights into the impact of globalization on labor standards and working conditions and will contribute to the ongoing debate on the implications of globalization for the labor market. Dhaka University Law Journal, 2023, 34 (2), 133-151